Receipt of specialized palliative care and health care utilization at the end of life in hematological cancer patients – the Stockholm experience - Lena von Bahr; Peter Strang; Torbjörn Schultz; Per Fürst (Acta Oncologica)
Background: The treatments of hematological malignancies tend to be intense, and compared with solid tumors, less is known about the health care consumption during end of life (EOL). Therefore, the aim was to study the receipt of specialized palliative care (SPC) and how it affects health care utilization, in relation to sex, age, socioeconomics, and frailty risk (Hospital Frailty Risk Score [HFRS]).